Piloting a new approach: making use of technology to present a distance learning computer science course - Tina Wilson; Denise Whitelock (Association for Learning Technology, 1996)
Teaching projects which make use of new technology are becoming of interest to all academic institutions in the UK due to economic pressure to increase student numbers. CMC (Computer- Mediated Communication) such as computer conferencing appears an attractive solution to higher education's 'numbers' problem, with the added benefit that it is free from time and place constraints. Researchers have discussed CMC from a number of different perspectives, for example Mason and Kaye (1989) describe a CMC system as a system of interactivity between tutors, students, resources and organizational structure. Steeples et al (1993) consider CMC in terms of group cohesion, modes of discourse and intervention strategies to stimulate and structure participation. Goodyear et al (1994) discuss the Just in Time (TT-Based) Open Learning (JTTOL) model in terms of a set of educational beliefs, role definitions, working methods and learning resources, together with a definition of infrastructure requirements for CMC. Shedletsky (1993) suggests that a CMC should be viewed in terms of an 'intrapersonal communication' model, while Mayes et al (1994) identify three types of learning which is mediated by telematics, that is, learning by conceptualization, construction and dialogue. Other researchers, such as Velayo (1994), describe the teacher as 'an active agent', and present a model for computer conferencing which neglects the social aspect of CMC, while Berge (1995) mentions the importance of social activity between students and the importance of the role of the moderator. From these accounts, there appear to be a number of dimensions which can be used to evaluate CMC. Not all researchers emphasize the same dimensions; however, this paper proposes that computer conferencing systems should be designed to encourage students to participate in all three of the following dimensions. These can be summarized as: (a) a knowledge dimension (includes domain and meta knowledge); (b) a social dimension; and (c) a motivational dimension. We will focus on the design and management of a conference M205-STILE, which was employed by the Open University's Computer Science department to supplement the teaching of an undergraduate course. The conference was structured into sub-conferences to take account of the above three dimensions and to facilitate students' computer-supported collaborative learning. This paper reports on the construction of the CMC environment, but more importantly how the three dimensions can be sustained through the role of a person whom we have called an Interactive Media Facilitator (IMF). This implementation is part of the 'Students' and Teachers' Integrated Learning Environment' (STILE) project.